A descriptive study of suspected perinatal asphyxia at Mitchells Plain District Hospital: A case series - Johannes P.J. Stofberg; Graeme W. Spittal; Tracey Hinkel; Tasleem Ras (South African Family Practice)
Background: South Africa aims to end all preventable deaths of children under the age of five as part of their commitment to the Sustainable Development Goals. More than half of these mortalities occur in the neonatal period with perinatal asphyxia as one of the leading causes. This study investigated and identified the characteristics of perinatal asphyxia and its contributing factors at a district hospital in Cape Town.